Does adherence to a motivational counseling program impact weight loss? - Ford, M. Allison; Haskins, Mary A.; Nahar, Vinayak K. (International Journal of Health Sciences, 2017)
Objective: Given the health-care cost and prevalence of preventative health disparities across today’s population, it is not surprising that the recent health-care legislation has aimed to address preventative health initiatives. Specifically, weight management counseling is a preventative health initiative that the affordable care act has emphasized. We evaluated motivational counseling (MC) for weight management in a college aged population and to what extent adherence to the program impacts the magnitude of weight loss. Methods: A total of 120 southeastern US college students from 2009 to 2013 participated in weekly counseling sessions lasting 15-30 min focused on weight management. Results: The study findings indicated a 51% greater weight loss in participants with greater adherence to the MC program. There were no differences across gender or race. Conclusion: These findings indicate that motivation counseling is an effect modality for addressing obesity-related preventive health disparities.